Rhizobium inoculation increases of bean and maize yields in intercrops on farms in the Peruvian Sierra - Pineda, P.; Kipe-Nolt, Judith A.; Rojas Alvarado, E. (Cambridge University Press, 1994)
Nitrogen deficiency severely limits production of the bean maize association grown by small-scale farmers in upland Peru. Sixty-four bean Rhizobium isolates were evaluated for induction of a plant growth response in pots of soil from the area and 14 of the most promising strains of these were tested on farmers' fields in 13 trials over a three year period. Bean yields were increased by inoculation with at least one Rhizobium strain in seven of the trials, with increases ranging from 0.21 to 0.68 t ha?1. Bean yields were not increased by the application of 120 kg N ha?1 to the intercrop. Maize yields were increased by Rhizobium inoculation in nine of the 13 trials by between 0.34 and 1.85 t ha?1. Maize responded to nitrogen fertilizer on the same nine farms. This Rhizobium selection strategy, although laborious, was effective in identifying strains that can be recommended for use as inoculants by farmers in the region.